Employee Embeddedness and Turnover Intentions: Exploring the Moderating Effects of Commute Time and Family Embeddedness - Purba, Debora Eflina (UI Scholars Hub, 2015)
This study aims to investigate the moderating effects of commute time, availability of nearby replacement jobs, and family embeddedness to the relationship between employee embeddedness and turnover intentions. Employee embeddedness includes organizational and community embeddedness. Previous studies showed that employee embeddedness is a good predictor of turnover. However, other studies have subsequently demonstrated different results in employee embeddedness-turnover relationship. The present study hypothesizes that commute time, availability of nearby replacement jobs, and family embeddedness moderate the relationship between employee embeddednessturnover intentions. Data were obtained from a sample of 330 full-time employed nurses in two hospitals in Jakarta, Indonesia. Results showed that commute time and family embeddedness moderated the organizational embeddednessturnover intention relationship. Availability of nearby replacement jobs did not moderate employee embeddedness turnover intentions. Theoretical and practical implications of the findings are discussed.